2014
DOI: 10.1088/0067-0049/213/2/31
|View full text |Cite
|
Sign up to set email alerts
|

LONG-TIMESCALE BEHAVIOR OF THE BLAZHKO EFFECT FROM RECTIFIED KEPLER DATA

Abstract: In order to benefit from the four year unprecedented precision of the Kepler data, we extracted light curves from the pixel photometric data of the Kepler space telescope for 15 Blazhko RR Lyrae stars. To collect all the flux from a given target as accurately as possible, we defined tailor-made apertures for each star and quarter. In some cases, the aperture finding process yielded sub-optimal results, because some flux have been lost even if the aperture contains all available pixels around the star. This fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
165
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(179 citation statements)
references
References 30 publications
13
165
1
Order By: Relevance
“…Accurate space data helped uncover various dynamical processes present only in modulated stars (for example, period doubling Kolláth et al 2011) and additional radial and non-radial modes Benkő et al 2014;Szabó et al 2014). Data from the ground-based surveys, on the other hand, are very useful for studying large samples statistically and investigating general and common characteristics of modulated stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate space data helped uncover various dynamical processes present only in modulated stars (for example, period doubling Kolláth et al 2011) and additional radial and non-radial modes Benkő et al 2014;Szabó et al 2014). Data from the ground-based surveys, on the other hand, are very useful for studying large samples statistically and investigating general and common characteristics of modulated stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jurcsik et al (2005a) showed that the modulation amplitude of short-pulsation-period RR Lyrae stars can be higher than for long-period stars. Benkő et al (2014) and Benkő & Szabó (2015) suggest a monotonic dependence between the strength of amplitude modulation and the period of the BL cycle (the longer the cycle, the larger the amplitude). While the upper limit of the modulation length is still unclear, the bottom limit is probably defined by the upper limit of the rotational velocity of a star.…”
Section: Introductionmentioning
confidence: 99%
“…In the power spectrum, it manifests as signals close to half-integer frequencies. This phenomenon was detected for the first time in RR Lyr from Kepler data ( [5]), and later studies showed that it affects many modulated RRab stars (see, e.g., [2,14] , first overtone and long-periodic variability forming a period ratio 0.68 are marked with pink crosses ( [7]), RR Lyrae stars with short-period signal are marked with yellow squares ( [9]) and RRab stars with another shortperiod signal are marked with blue filled circles ( [10]). Blazhko stars with additional signals from our sample are marked with orange symbols.…”
Section: Resultsmentioning
confidence: 87%
“…K2 is a bona fide community endeavour: without a central, pre-determined research plan, exoplanets, stellar (asteroseismic and other variable) sources, extragalactic objects, microlensing events, and even Solar System objects have been proposed by community members. 1 This opened up new possibilities in RR Lyrae research, too, since compared to the original Kepler field, where roughly 50 RR Lyrae stars were found ( [1,6,7]), thousands of RR Lyrae stars can be observed with K2. Members of the Kepler Asteroseismic Science Consortium (KASC) RR Lyrae and Cepheids Working Group initiated a large survey to ensure that as many RR Lyrae stars will be observed with K2 as possible.…”
Section: Introductionmentioning
confidence: 99%